Application of Electric Cone Penetration Test in Unconsolidated and Consolidated Sediments. (2016) - Gopinath, Girish
Abstract: Landfill areas have received significant emphasis by the geo-technical community in the recent years as large structures are being built in these sensitive areas due to the scarcity of land in the urban area. The high cost of these structures has dictated the need for accurate and precise strength measurement as a basis for improving foundation design, efficiency, safety and sediment stability analyses. Specific analyses of shear strength of the soil and ground improvement methods are necessary to stabilize the ground more economically, prior to the early stage of construction especially if it is done in a reclamated land. During past two decades, Cone Penetration Test (CPT) gained importance as a preferred versatile device for carrying in-situ sub-surface investigations and for characterization of soils. CPT readings which are continuous in nature are best considered than conventional rotary drilling, which allows clear delineation of the strata, depth, thickness, and extent of the soil. In certain conditions, the cone penetrometer technology is used in delineating and detecting anomalous conditions or features which are present on the surface in unusual condition. This can be penetrated in most of the soil types, which ranging from soft clays to hard clays to greater depth beneath the surface. CPT provides data for estimating engineering properties of soil which intended to help with the design and construction of earthworks, foundation for structures, and the behaviour of soils under static and dynamic loads. This conveys the advantage of electric cone penetration test in the reclaimed land, and highly recommendable in unconsolidated and consolidated sediments. In the present investigation, electric cone penetration test carried out in the unconsolidated sediments of reclamated land in Dubai, UAE.